The Fulfilment of Workers' Rights in the Dimension of Human Rights based on Indonesian Manpower Law - Imron, Ali; Hunawa, Hermawan Rizki (IJCLS (Indonesian Journal of Criminal Law Studies), 2021)
which is regulated in Article 88 paragraph (1) in Law Number 13 of 2003 concerning manpower. However, in reality there are still many companies that ignore the rights of their workers' wages, which should be a normative right that must be fulfilled by the employers of the workers themselves. There are still many companies that fulfill the rights of workers / laborers themselves, which are still very concerning and there are still many companies that ignore the rights of the workers themselves. Which in itself is a current employment problem. And we often see that many layoffs that occur in Indonesia are caused by the dissatisfaction of an entrepreneur with the performance of his workers. In this case it is due to the unfulfilled rights of the workers themselves, especially from the fulfillment of wage or salary rights. With the fulfillment of workers' rights, this can have many positive impacts that occur between employers and workers themselves. In addition to enhancing the harmonious relationship between employers and workers, this can improve the welfare of the workers' economy and will show a good quality of performance for the company and devote all their loyalty to the company. Before carrying out work where the employer provides it, it is necessary to establish a work agreement and a collective labor agreement between the employer and the worker, in which this is done to protect what should be the right of both parties. And no less important, the problem related to the field of occupational health, is that during a work relationship which is a legal relationship, workers must receive insurance for their health.